2018
DOI: 10.1161/jaha.118.008976
|View full text |Cite
|
Sign up to set email alerts
|

Is Baseline Orthostatic Hypotension Associated With a Decline in Global Cognitive Performance at 4‐Year Follow‐Up? Data From TILDA (The Irish Longitudinal Study on Ageing)

Abstract: Background It is postulated that orthostatic hypotension ( OH ), a reduction in blood pressure (≥20/10 mm Hg) within 3 minutes of standing, may increase cognitive decline because of cerebral hypoperfusion. This study assesses the impact of OH on global cognition at 4‐year follow‐up, and the impact of age and hypertension on this association. Methods and Results Data from waves 1 and 3 of TILDA (The Irish Longitudinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 49 publications
0
32
0
Order By: Relevance
“…Our study, a substudy of the larger Nilvad trial, is limited by its small sample size, hampering the addition of relevant covariates such as hypertension ( 48 ). However, our study is enhanced, also compared with the larger Nilvad trial, by the detailed and thorough BP measurements and characterization of participants, including cerebral imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Our study, a substudy of the larger Nilvad trial, is limited by its small sample size, hampering the addition of relevant covariates such as hypertension ( 48 ). However, our study is enhanced, also compared with the larger Nilvad trial, by the detailed and thorough BP measurements and characterization of participants, including cerebral imaging.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of OH on cognitive function remains contradictory in the literature depending on the age group, test battery (screening tool versus comprehensive multi-domain testing), covariates and study design. Several cross-sectional studies showed either no association with global cognitive function [3,10,11] or a significant association in terms of global cognitive decline [2,4,[12][13][14]. In a long-term analysis of the Rotterdam study, Wolters et al reported a higher risk of Alzheimer's disease and vascular dementia in participants with OH [15].…”
Section: Introductionmentioning
confidence: 99%
“…Orthostatic hypotension (OH), classically defined as a sustained drop of more than 20 mm Hg for systolic blood pressure (SBP) and/or more than 10 mm Hg for diastolic blood pressure (DBP) three minutes after standing upright or during a head-up tilt, 1,2 has been associated with an increased risk of cardiovascular disease. In fact, previous studies have reported a significant association of OH with cardiovascular morbidity and mortality, 3,4 atrial fibrillation, 5 cognitive decline, 6 among other clinical conditions. Being strongly associated with aging 7 and with the current demographic trends showing an increase in the proportion of the population above 65 years of age, the burden of OH is also expected to increase and contribute to a greater risk of falling, disability and reduced quality of life in the elderly.…”
Section: Commentarymentioning
confidence: 99%